Mega shopping malls technology-enabled facilities, destination image, tourists’ behavior and revisit intentions: Implications of the SOR theory - Al-Sulaiti, Ibrahim (Frontiers in Environmental Science, 2022)
Mega shopping malls' technology-enabled services influence tourists' shopping behavior as Jumbo malls offers a broader range of products and services with innovative features that impact revisit intentions. This study's novelty is the research on mega shopping malls as literature lacs it. Travel, leisure, and tourism sectors have gained balanced attention, and scholars have contributed with academic research perspectives. Mega malls in modern cities attract tourists that help foster economic development with revisit intentions. Technology-enabled products influence sustainable tourist experiences. Despite broad investigative studies on tourists' experiences, literature shows little regarding tourists' shopping experiences in mega shopping malls that lead to reviewing tourist destination choices. This narrative research explores how shopping mall attributes influence tourists' behavioral intentions in mega malls' shopping environments that satisfy them for revisiting intentions in the future. Doha city is an economic hub that plays a crucial role in the economic and social development of the region. The city lies on the sea and has many mega shopping malls that offer technology-enabled products and services to attract regional and global tourists. It boosts sustainable economic activities, climate change, and environmental protection concerns. The city of Doha oscillates widespread beaches, and its mega shopping malls are famous as tourist attractions for domestic, regional, and global travelers. As an independent and economically affluent country, it has its take on attracting tourists. The study aimed to examine the revisiting behavior of Doha tourists with destination revisit intentions. A pleasant shopping experience in sizeable technology-enabled shopping malls is critical for tourist satisfaction. The trust, perceived value, and environmental effects affect tourists' revisit intentions. Other factors include high spirits, excitement, new tourist destinations, and visiting friends. External factors include a preference for natural and historical destinations, technology-enabled facilities, infrastructure, safety, affordability, comfort, budget range, and sociocultural factors. The study recommends future inquiries based on factors that empirically test mega malls' technology-enabled product effects on tourists' behaviors. The findings not only contribute to tourists' experiences in mega shopping malls and revisit intention literature but also provide implications' for officials and policymakers to articulate policies that promote tourists' mega-mall shopping experiences and destinations.